Iqra' As the Beginning of Civilization Transformation Thematic Interpretation of QS. Al Alaq Verses 1-5 - Avicena, Fayiz Yan; Azizah, Alfiyatul (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Surah Al-'Alaq verses 1-5, the first revelation to Prophet Muhammad SAW, underscores the foundational command to "read" as a transformative directive for human civilization. This study explores the profound significance of Iqra' through a thematic interpretation, emphasizing its role in advancing intellectual and spiritual dimensions. The research identifies contemporary challenges such as literacy gaps, limited Muslim contributions to modern knowledge, and the need for integrative education as issues that Iqra' seeks to address.The study employs library research methodology, focusing on thematic exegesis (tafsir maudhū'i) to analyze the verses systematically. Using both primary sources, such as classical tafsir texts, and secondary sources, the analysis highlights the comprehensive meaning of Iqra'-from gathering information to fostering spiritual growth, thereby linking intellectual pursuits with moral integrity.Findings indicate that Iqra' forms the foundation of knowledge acquisition, enabling humans to comprehend the essence of creation, nurture ethical conduct, and fulfill their roles as stewards on Earth. The emphasis on the pen (qalam) in verse 4 signifies the centrality of written knowledge in preserving and disseminating civilization's legacy. Furthermore, Iqra' reinforces collective awareness among Muslims to pursue and share knowledge, serving as a response to modern literacy and technological challenges.The study concludes that Iqra' transcends its textual dimension, advocating a holistic integration of intellect and faith to navigate contemporary issues. It reaffirms the imperative for Muslims to align advancements in science and technology with spiritual values, ensuring the development of a balanced and dignified civilizations.